Hubungan antara Work-Family Conflict dan Keterikatan Kerja pada Ibu Bekerja - Handini, Rimba Eka; Haryoko, Siti Farida; Yulianto, Aries (Noetic Psychology, 2014)
AbstractÃÂ This research was conducted to find relationship between work-family conflict and work engagement among working mother. Work-family conflict was measured using Work-Family Conflict Scale (Carlson, Derr, & Wadsworth, 2003) and work-engagement was measured using Utrecth Work- Engagement Scale (Schaufeli, Bakker, & Salanova, 2006). The participants were 72 mothers who work in the formal sector, both public servant and private sector employees. The main result of this research showed that work-family conflict doesnÃ¢â¬â¢t have a significant correlation with work engagement among working mother, r (70) = -.080; p > .05. ÃÂ Keywords: Work-family conflict, work engagement, working motherÃÂ